Working at the margins: early medieval activity at Long Lane, Stoke Holy Cross, Norfolk - White, Joshua; Ames, John; Anderson, Sue; Sillwood, Rebecca; Fryer, Val; Dobson, David (Medieval Settlement Research, 2021)
Pre-development excavations in the village of Stoke Holy Cross, Norfolk, discovered an area demarcated by ditches within which the remains of apparent agrarian or industrial activity dating from the 11th-12th centuries were identified. These remains add to the corpus of early medieval rural sites known from the region, and have the potential to inform future assessments of early manorial systems and the nature of rural industrial activities undertaken around the time of the Norman Conquest.